Strategi Pemasaran pada Pedagang Kaki Lima Gentala Arasy Jambi Pasca COVID-19 - Masruriyah, Andi; Nazori, M.; Ifazah, Laily (Lembaga Yasin AlSys, 2024)
This study aims to determine the strategies implemented by street vendors after Covid-19 and the obstacles or obstacles faced by street vendors in selling after Covid-19. The type of research used in this research is qualitative. The location of this research was carried out in the gentala arasy bridge area, which is one of the livelihood places for a large number of street vendors. The data sources used in this research are primary and secondary data. Based on the results of research and discussion that has been described in the previous chapter, it can be concluded that: The strategies carried out by street vendors in the gentala arasy area after Covid-19 are: Maintaining product quality which means maintaining cleanliness and taste. The obstacles faced by street vendors in selling can be seen from two internal and external factors, where from internal aspen is the location and business mudal, while from external aspen is weather such as the rainy season.